The Role of External Oversight in The Organization of Policy Import: A model of Supreme Audit (Journal of Accounting and Financial Studies ( JAFS ), 2019)
The construction of development is required to develop various economic sectors with the necessity to meet the various requirement of both individuals and institutions , or through the import process , which must be commensurate with the needs of the market and the economy and development. But in fact , we find that the process of import in Iraq after 2003 took a turn dangerous excesses on limits of philosophy and objectives of the import , which is reflected at the level of national production as well as the policy of dumping and given and the lack of matching a lot of goods and materials imported for Standards and Measures of quality and stands behind it causes many of them exposure to the market and weak sectors with an overlap between the import and spread of the phenomenon of corruption . Highlights the importance of research by studying the reality of the import process in Iraq and to identify those responsible for the import process knowledge of the mechanisms of control of foreign policy to regulate the import and reduce the phenomenon of financial and administrative corruption . The study found many of the recommendations which will help to protect the product , the market and the national economy and the achievement of development and needs as well as the creation of mechanisms to combat corruption